Beware of workaholics: household preferences and individual equilibrium utility - Gersbach, Hans; Haller, Hans (Discussion paper series, 2005)
This paper analyzes the effects of sociological changes in the form of a shift of influence within two-member households participating in labor and product markets. The most striking effects occur when household members differ in individual preferences and enjoy positive leisure-dependent externalities. For instance, a global sociological change where the workaholic" member becomes more influential in each working class household can render the working class worse off. A binding restriction on the number of hours an individual is allowed to work can benefit all workers.
Keywords: Arbeitspapier; Graue Literatur